Enterohemorrhagic Escherichia coli O157:H7 Infection Inhibits Host Endoplasmic Reticulum Stress in Intestinal Epithelial Cells via the PERK Pathway - Litai Xu; Song Liang; Yaoguo Wang; Min Gao; Bao Zhang; Wei Zhao; Ying Hua; Chengsong Wan (Pathogens)
Enterohemorrhagic Escherichia coli (EHEC) O157:H7 is a foodborne pathogen that causes a variety of diseases, ranging from self-limiting gastroenteritis to life-threatening extra-intestinal diseases such as hemolytic uremic syndrome. EspF, an effector protein secreted by the type III secretion system of EHEC, is primarily responsible for the development of inflammatory colitis. Our previous study revealed that EspF interacts with the host Annexin A6 (ANXA6) protein and targets the endoplasmic reticulum (ER). Given the critical effects of ER stress on the host responses of gastroenteritis, we explored the role of EspF–ANXA6 interaction in ER stress. Caco-2 cells were infected with different strains of EHEC and transfected with modified plasmids to establish in vitro research models. Our results revealed that infection with espF-deletion EHEC strains significantly exacerbated ER stress. Specifically, the phosphorylation of eIF2α was elevated, and the expression levels of BiP, ATF4, and CHOP were increased by more than 15% compared to those in cells infected with wild-type EHEC strains. Further experiments showed that EspF co-localizes with BiP and down-regulates the PERK pathway. Meanwhile, the EspF–ANXA6 interaction could aggravate the inhibition of the PERK pathway and stimulate calcium influx to disturb ER homeostasis, eventually leading to apoptosis. Our findings suggest that the EspF–ANXA6 interaction could inhibit ER stress through the PERK pathway, which may limit cell-to-cell communication and block the clearance of bacteria in host cells.